PERSEPSI PASIEN TERHADAP EDUKASI PRAOPERATIF PADA TINDAKAN BEDAH ELEKTIF: SEBUAH STUDI KUALITATIF: PATIENT PERCEPTIONS OF PREOPERATIVE EDUCATION IN ELECTIVE SURGERY: A QUALITATIVE STUDY - Handi Efendi; Zaim Anshari (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Preoperative education in elective surgery is a crucial nursing intervention to reduce anxiety and enhance patient readiness. However, patients' perceptions of the education they receive are often not adequately explored. This study aims to explore patient perceptions of preoperative education for elective surgery at Dr. Pirngadi Regional Hospital, Medan. This study employed a qualitative approach with a descriptive phenomenological design. Eight participants were selected through purposive sampling based on inclusion criteria. Data were collected through semi-structured in-depth interviews until saturation was reached. Data analysis used Braun and Clarke's thematic analysis. Three main themes were identified: (1) a gap between expectations and reality of information, where education was procedural, limited, and rushed; (2) the vital role of family support in building readiness, yet not formally accommodated; (3) preferences for contextual and empathetic educational methods, including visual aids, polite and local language, and staged delivery. Patients' perceptions indicate that preoperative education at Dr. Pirngadi Regional Hospital, Medan, remains not patient- and family-centered. Hospitals need to develop multimodal education standard procedures, involve families, and enhance nurses' empathetic communication to improve the quality of the perioperative experience. AbstrakEdukasi praoperatif pada tindakan bedah elektif merupakan intervensi keperawatan penting untuk mengurangi kecemasan dan meningkatkan kesiapan pasien. Namun, persepsi pasien terhadap edukasi yang diterima seringkali tidak tergali secara memadai. Penelitian ini bertujuan untuk mengeksplorasi persepsi pasien terhadap edukasi praoperatif pada tindakan bedah elektif di RSUD Dr. Pirngadi Medan. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan desain fenomenologi deskriptif. Partisipan berjumlah 8 orang yang dipilih secara purposive sampling sesuai kriteria inklusi. Pengumpulan data dilakukan melalui wawancara mendalam semi-terstruktur hingga mencapai titik jenuh. Analisis data menggunakan analisis tematik Braun dan Clarke. Ditemukan tiga tema utama: (1) kesenjangan antara harapan dan realitas informasi, di mana edukasi bersifat prosedural, terbatas, dan terburu-buru; (2) peran vital dukungan keluarga dalam membangun kesiapan, namun belum diakomodasi secara formal; (3) preferensi metode edukasi yang kontekstual dan empatik, meliputi media visual, bahasa santun dan lokal, serta penyampaian bertahap. Persepsi pasien menunjukkan bahwa edukasi praoperatif di RSUD Dr. Pirngadi Medan masih belum berpusat pada pasien dan keluarga. Rumah sakit perlu menyusun standar prosedur edukasi multimodal, melibatkan keluarga, serta meningkatkan komunikasi empatik perawat untuk meningkatkan kualitas pengalaman perioperatif.